Urgensi Penerapan Prinsip Manjemen Modern Pada Lembaga Pendidikan Islam - Muhammad Raihan Nasucha; Mochamad Fikri Alby Rapsjani; Ditya Mareta Ayu Puspitasari (Lembaga Publikasi Ilmiah, 2021)
The success of an educational institution cannot be separated from the management system that regulates all educational activities in it properly. Modern management principles are the key to success and provide various innovations and new breakthroughs in the governance of an educational institution. It is important for Islamic educational institutions to participate in implementing a modern management system that manages the various educational needs of an institution. With the application of good modern management principles in Islamic educational institutions and institutions, it will have a tremendous positive impact on the progress of these institutions. Efficiency and effectiveness will be obtained by Islamic education institutions in the education management system which will later help achieve the goals of Islamic education to be achieved. ABSTRAK Keberhasilan sebuah lembaga pendidikan tidak dapat dilepaskan dari sistem manajemen yang mengatur segala aktivitas pendidikan didalamnya dengan baik. Prinsip manajemen modern menjadi kunci keberhasilan serta memberikan berbagai inovasi dan terobosan baru di dalam tata kelola sebuah lembaga pendidikan. Penting bagi lembaga pendidikan Islam untuk ikut serta dalam menerapkan sistem manajemen modern yang mengelola berbagai kebutuhan pendidikan dalam sebuah institusi. Dengan penerapan prinsip manajemen modern yang baik dalam lembaga dan institusi pendidikan Islam akan memberikan dampak positif yang luar biasa untuk kemajuan lembaga tersebut. keefisiensian dan keefektifan akan didapatkan oleh lembaga pendidikan Islam dalam sistem pengelolaan pendidikan yang nantinya akan membantu mencapai tujuan pendidikan Islam yang hendak dicapai.